Human health risk assessment associated with the consumption of mussels (Perna perna) and oysters (Crassostrea rhizophorae) contaminated with metals and arsenic in the estuarine channel of Vitória Bay (ES), Southeast Brazil. (November 2021) - Vieira, K.S.; Delgado, J.F.; Lima, L.S.; Souza, P.F.; Crapez, M.A.C.; Correa, T.R.; Aguiar, V.M.C.; Baptista Neto, J.A.; Fonseca, E.M.
Abstract: The estuarine channel of Vitória Bay was evaluated regarding bioaccumulation of metals (Al, Ba, Mn, Fe, Zn, Cu, Cr, Pb, Ni, Cd, Hg) and As in mollusks. Mussels from an aquaculture farm and transplanted into the estuary, whereas oysters were collected in situ in the same area. Concentrations of Al, Mn, Fe, Cr and As were higher in P . perna, whereas C . rhizophorae bioaccumulated more Ba, Zn and Cu. Arsenic concentrations in P . perna exceeded the limit of the Brazilian legislation in the outer estuary. Salinity seemed to influence metal uptake differently for each bivalve, with P . perna absorbing more metal at higher salinities and C . rhizophorae in areas of lower salinity. Hazard index (HI) >1 revealed risk for both bivalves for high level consumers. Target Cancer Risk (TCR) for As revealed threat for human health associated with the consumption of mussels and oysters from the study area. Highlights: The estuarine port channel of Vitória (ES), Brazil, was evaluated for metal pollution Mussel Perna perna and oyster Crassostrea Rizophorae were used as biomonitors Al, Ba, Zn, Cr, Cu, Pb, As, Mn, Fe, Pb, Ni, Cd, Hg were analyzed in bivalves' tissues Estimated Daily Intake, Hazard Index (HI), Target Cancer risk (TCR) were used HI and TCR revealed health risk for consumption of mussels and oysters